The Effect of Geographical Conditions on the Role of the Special Autonomy Fund for the Availability of Road Infrastructure in Papua - Saktina, Renny; Khoirunnurrofik, Khoirunnurrofik (Jurnal Bina Praja, 2022)
This study identifies the relationship of the Special Autonomy Fund (DOK) to Road Infrastructure by looking at variations in the Construction Cost Index as a proxy that describes the geographical conditions in Papua. Infrastructure development is a sector that is expected to accelerate the provision of basic infrastructure to reduce the development gap. However, the success of infrastructure development in Papua is inseparable from geographical factors. By using data from 29 regencies/cities in Papua Province and 11 regencies/cities in West Papua Province from 2010 to 2020, to determine the correlation of the Special Autonomy Fund on Road Infrastructure, the fixed effect panel data method and the moderating regression model were used to see if the moderating variable Construction Cost Index can strengthen or weaken the relationship of the Special Autonomy Fund to Road Infrastructure. This study found a positive relationship between the Special Autonomy Fund on Road Infrastructure and identified a negative moderating of the Construction Cost Index variable on the relationship of the Special Autonomy Fund to Road Infrastructure. This shows that the higher the Construction Cost Index, the higher the price of construction materials, increasing the total cost of road infrastructure development. As a result, the Special Autonomy Fund allocated is only able to buy fewer road construction materials, which has an impact on the reduced quantity of road infrastructure built in the provinces of Papua and West Papua.